Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I wonder how to prove ? $$\prod_{k=1}^{n}\left(1+2\cos\frac{2\pi 3^k}{3^n+1} \right)=1$$ give me a tip

share|cite|improve this question
Source?${}{}{}$ – Gerry Myerson Jan 23 '13 at 12:20
@GerryMyerson - do you suspect this question shouldn't be answered? – nbubis Jan 23 '13 at 12:32
@nbubis, I just like to know where questions come from before I put a lot of time into them. If, for example, the statement is false, I don't want to waste a lot of time trying to prove it --- so I'd like some reason for believing it's true, some source, some reference. – Gerry Myerson Jan 23 '13 at 12:42

Hint: First prove that: $$\prod_{k=0}^n\left(1+2\cos(3^k x)\right) = 1 + 2\sum_{k=1}^{m}\cos(kx)$$ Where: $$m=\sum_{k=0}^n{3^k} = \frac{3^{1+n}-1}{2}$$

Then show that you are essentially sampling the $\cos$ function between $0$ and $2\pi$ at equal intervals, and since the average is equal to zero, the sum is therefore $1$, as required. To prove the first identity, you can use the Chebyshev relation: $$\cos(nx)=2\cos(x)\cos((n-1)x)-\cos((n-2)x)$$

share|cite|improve this answer
thanks!! First prove ??(very difficult) $$\prod_{k=0}^n\left(1+2\cos(3^k x)\right) = 1 + 2\sum_{k=1}^{m}\cos(kx)$$ – Young Jan 23 '13 at 13:49
@user59343 - you asked for a tip.. as I said, you can get this using the Chebyshev relation and starting from the left hand side. – nbubis Jan 23 '13 at 13:52
@user59343 - is that a question? please try to use english as well. – nbubis Jan 23 '13 at 16:27
is it true? $$\sum_{k=1}^{ \frac{3^{1+n}-1}{2}} \cos kx=0$$ where $x=\frac{2\pi}{3^n+1}$ – Young Jan 23 '13 at 16:31
Dear nbubis. I'm sorry. The essence of the previous question is that how I can finish the proof from the first Identity – Young Jan 23 '13 at 16:49

Let $S_n = \sum_{k=0}^n 3^k = \frac{3^{n+1}-1}{2}$. Then

$$3^{n}- S_{n-1} = 3^{n} - \frac{3^{n}-1}{2} = \frac{3^{n}+1}{2} = S_{n-1}+1. $$

Now by induction we have the following product identity for $n \geq 0$:

$$ \begin{eqnarray} \prod_{k=0}^{n}\left(z^{3^k}+1+z^{-3^k}\right) &=& \left(z^{3^{n}}+1+z^{-3^{n}}\right)\prod_{k=0}^{n-1}\left(z^{3^k}+1+z^{-3^k}\right) \\ &=& \left(z^{3^{n}}+1+z^{-3^{n}}\right) \left(\sum_{k=-S_{n-1}}^{S_{n-1}} z^k\right) \\ &=&\sum_{k=S_{n-1}+1}^{S_n}z^k + \sum_{k=-S_{n-1}}^{S_{n-1}}z^k+\sum_{k=-S_n}^{-S_{n-1}-1} z^k \\ &=& \sum_{k=-S_n}^{S_n} z^k \end{eqnarray} $$

Now take $z = \exp\left(\frac{\pi \, i}{3^n + 1}\right)$ and use that $z^{3^n+1}=-1$ to get

$$\begin{eqnarray} \prod_{k=0}^n\left(1 + 2 \cos \left(\frac{2 \pi \,3^k}{3^n+1}\right)\right) &=& \sum_{k=-S_n}^{S_n}z^{2k} = \frac{z^{2S_n+1}-z^{-2S_n-1}}{z-z^{-1}} = \frac{z^{3^{n+1}}-z^{-3^{n+1}}}{z-z^{-1}} \\ &=& \frac{z^{3(3^n+1)-3} - z^{-3(3^n+1)+3}}{z-z^{-1}} = \frac{z^3-z^{-3}}{z-z^{-1}} = z^2 + 1 + z^{-2} \\ &=& 1 + 2\cos\left(\frac{2\pi}{3^n+1}\right) \end{eqnarray}$$

and your identity follows.

share|cite|improve this answer
But the identity in the OP says that the big product is equal to $1$, while your identity says it is equal to $1 + 2\cos\left(\frac{2\pi}{3^n+1}\right)$ ? – Ewan Delanoy Jan 26 '13 at 15:51
@EwanDelanoy look at the range of the index $k$. – WimC Jan 26 '13 at 15:52
indeed. One slightly different index changes everything ... – Ewan Delanoy Jan 26 '13 at 15:55

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.